Application Of Artificial Intelligence And Information And Communication Technologies In Prevention Of Cyberattacks On Critical Infrastructure Facilities - Filipenko, Nataliia; Kupriіanova Anastasiіa; Ivanović, Aleksandar (Archives of Criminology and Forensic Sciences, 2024)
The article attempts to scientifically analyze certain aspects of unlawful (terrorist) influence on critical infrastructure and life support facilities in Ukraine. This research relevance is due to the real need to improve measures to counter cyber-terrorist attacks using the capabilities of artificial intelligence and information and communication technologies in order to create effective scientific and practical methods.